Analysis of the kinetic of expression of tristetraprolin and HuR by rheumatoid arthritis patients pheripheral blood mononuclear cells stimulated with lipopolysaccharide - M. Fabris; B. Tolusso; E. Gremese; P. Tomietto; G. Ferraccioli (PAGEPress Publications, 2004)
Objective. Given the role of TNF-α in Rheumatoid Arthritis (RA) we decided to define the characteristics of the TNF- α synthesis by peripheral blood mononuclear cells (PBMNCs) obtained from active-aggressive RA patients giving a particular attention to the modulation of the expression of two fundamental proteins in TNF-α mRNA stability regulation, Tristetraprolin (TTP) and HuR. Methods. 11 RA patients with active disease were enrolled in the study before their entry in 2 double blind protocols: Infliximab versus MTX and Etanercept versus MTX. 9 healthy blood donors were taken as controls. PBMNCs obtained by Ficoll centrifugation and plastic adherence were stimulated with lipopolysaccharide (LPS) and TNF-α was measured in the supernatant during 8 hours by ELISA. At each time point the cells were harvested and analysed for TNF- α, TTP and HuR mRNA expression by semi-quantitative PCR. Results. MNCs TNF-α secretion after LPS stimulation did not differ significantly between RA and control subjects, even if a tendency towards a more prompt response was observed in the patients. More importantly only the DMARDs responsive patients (DAS <3.7 at the 6th month, with a minimal reduction of 1.2 points) disclosed precociously (at the first month) a significant change in the profile of TNF-α secretion and maintained it until the 6th month. The "normalization" of the synthetic behaviour was accompanied by the resetting in the regulation of the expression of the TTP, that appeared significantly different in the patients before and after therapy. Conclusions. Independently from the type of therapy, responsive patients demonstrate a rapid change in the cellular biology at the systemic level that might drive the resolution of the phlogistic process at the synovial level.